Why Energy Taxes Face Opposition: Household Vulnerability and Price-ShockStress Pathways - Tasya Nayada; Daryono, Daryono, (Inovasi Analisis Data, 2025)
Purpose – To explain public support for energy taxes through behavioral, institutional, and psychological mechanisms beyondcost-based accounts.Design/methodology/approach – Survey-based structural equation modeling tests direct, mediated, and moderated pathwayslinking perceptions, household responses, and policy support.Findings – Perceived tax burdens reduce support mainly through sequential increases in household vulnerability and price-shockstress, while fairness and institutional trust directly enhance support and indirectly buffer insecurity. Climate concern and energyliteracy raise acceptance largely by reducing vulnerability and stress rather than operating solely as normative justifications.Proposed moderation by household responsibility roles is not supported, indicating that stress-related mechanisms operatebroadly across households rather than being strongly conditional on role-based exposure.Originality/value – This study advances a behavioral–institutional model that reframes the political cost of energy taxation as apsychological process in which insecurity and stress transmit burdens into opposition. By empirically establishing vulnerabilityand price-shock stress as central serial mediators, it moves the literature beyond direct-effect explanations and clarifies howinstitutional and cognitive resources function as resilience-building channels that sustain policy legitimacy.Research implications – Acceptance-oriented tax design should combine targeted compensation, credible governance, andcommunication strategies that reduce perceived insecurity and stress, thereby improving legitimacy and feasibility of energytaxes.